Interoception and Positive Symptoms in Schizophrenia - Ardizzi, Martina; Ambrosecchia, Marianna; Buratta, Livia; Ferri, Francesca; Peciccia, Maurizio; Donnari, Simone; Mazzeschi, Claudia; Gallese, Vittorio (Frontiers in Human Neuroscience, 2016)
The present study focuses on the multifaceted concept of self-disturbance in schizophrenia, adding knowledge about a not yet investigated aspect, which is the interoceptive accuracy. Starting from the assumption that interoceptive accuracy requires an intact sense of self, which otherwise was proved to be altered in schizophrenia, the aim of the present study was to explore interoceptive accuracy in a group of schizophrenia patients, compared to healthy controls. Furthermore, the possible association between interoceptive accuracy and patients’ positive and negative symptomatology was assessed. To pursue these goals, a group of 23 schizophrenia patients and a group of 23 healthy controls performed a heartbeat perception task. Patients’ symptomatology was assessed by means of the Positive and Negative Syndrome Scale (PANSS). Results demonstrated significantly lower interoceptive accuracy in schizophrenia patients compared to healthy controls. This difference was not accounted for participants’ age, BMI, anxiety levels and heart rate. Furthermore, patients’ illness severity, attention and pharmacological treatment did not influence their interoceptive accuracy levels. Interestingly, a strong positive relation between interoceptive accuracy and positive symptoms severity, especially Grandiosity, was found. The present results demonstrate for the first time that interoceptive accuracy is altered in schizophrenia. Furthermore, they prove a specific association between interoceptive accuracy and positive symptomatology, suggesting that the symptom Grandiosity might be protective against an altered basic sense of self in patients characterized by higher sensibility to their inner bodily sensations.